Species richness and the dynamics of coral cover in Bangka Belitung Islands, Indonesia - Tri Aryono Hadi; Rizkie Satriya Utama; Tri Arfianti (PeerJ, 2023)
Pressures on the world’s tropical coral reefs that threaten their existence have been reported worldwide due to many stressors. Loss of coral cover and declines in coral richness are two of the most common changes often reported in coral reefs. However, a precise estimate of species richness and the coral cover dynamics for most Indonesian regions, particularly in the Bangka Belitung Islands, have been poorly documented. Annual monitoring data from 2015 to 2018 at 11 fixed sites in the Bangka Belitung Islands using the photo quadrat transect method identified 342 coral species from 63 genera. Of these, 231 species (>65%) were rare or uncommon, occurring in <40% of all sites. The species richness of hard corals was categorized as moderate compared to other studies in Indonesia, averaging 53 species across sites and years, and there was an increasing number of sites with high species richness. The percent cover of live and dead hard corals was greater than other benthic and substrate categories in all sites; revealing a live-dead hard corals pattern with dead coral cover averaged 12% higher than live hard coral across the years, but they did not show a significant difference (P > 0.05). There was a slightly increasing trend in hard coral cover in ten out of 11 sites in 2018, indicating the reefs are in a recovery process. The results support the need to identify recovering or stable areas despite apparent anthropogenic and natural variations recently. This vital information is essential for early detection and preparation for management strategies in the current context of climate change and for ensuring future coral reef survival.